COLLABORATION ON RESEARCH METHODOLOGY TRAINING THROUGH VISITING MALAYSIAN PROFESSORS FOR LECTURERS IN INDONESIA - Yahya, Wachid; Sari, Anditha; Shidiq, Muhammad Agus; Burhanudin, Burhanudin; Muhamad, Wan Mansor Wan (Bengawan : Jurnal Pengabdian Masyarakat, 2024)
Improving the quality of research and development in the manufacturing industry is the main focus in the community service entitled "Collaborative Research Methodology Training Through Visiting Professor Malaysia for Lecturers in Indonesia". The initiation of this collaboration was carried out by the Politeknik Indonusa Surakarta, Pancasakti University Tegal, and STT Warga as a response to concerns about the quality of research by lecturers and students in Indonesia. Through research carried out by lecturers and students, whether in final assignments, theses, theses or dissertations, it is hoped that there will be increased academic activity and a deeper understanding of current developments in the manufacturing industry. In order to achieve this goal, this program involves visiting professors from Malaysia to provide research methodology training to lecturers in Indonesia. Through this collaboration, it is hoped that synergy will be created between the visiting professor's experience and knowledge and the local Indonesian context. It is hoped that this training will be able to improve the quality of research carried out by lecturers, so that it can make a positive contribution to the development of the manufacturing industry in Indonesia. Thus, this collaboration is a strategic step in improving academic quality and research contribution to the development of the manufacturing industry in Indonesia.